Charm fragmentation fractions and [Formula omitted] cross section in p-Pb collisions at [Formula omitted] - Acharya, S; Adamová, D; Agarwal, A; Aglieri Rinella, G; Aglietta, L; Agnello, M; Agrawal, N (The European physical journal. C, Particles and fields, 2024)
The total charm-quark production cross section per unit of rapidity [Formula omitted], and the fragmentation fractions of charm quarks to different charm-hadron species [Formula omitted], are measured for the first time in p-Pb collisions at [Formula omitted] at midrapidity ( [Formula omitted] in the centre-of-mass frame) using data collected by ALICE at the CERN LHC. The results are obtained based on all the available measurements of prompt production of ground-state charm-hadron species: [Formula omitted], [Formula omitted], [Formula omitted], and [Formula omitted] mesons, and [Formula omitted] and [Formula omitted] baryons. The resulting cross section is [Formula omitted], which is consistent with a binary scaling of pQCD calculations from pp collisions. The measured fragmentation fractions are compatible with those measured in pp collisions at [Formula omitted] and 13 TeV, showing an increase in the relative production rates of charm baryons with respect to charm mesons in pp and p-Pb collisions compared with [Formula omitted] and [Formula omitted] collisions. The [Formula omitted]-integrated nuclear modification factor of charm quarks, [Formula omitted], is found to be consistent with unity and with theoretical predictions including nuclear modifications of the parton distribution functions.